Three-Dimensional Metacomposite Based on Different Ferromagnetic Microwire Spacing for Electromagnetic Shielding - QIAO Ye; JIANG Qian; UDDIN Azim; QIN Faxiang; WU Liwei (东华大学学报（英文版）, 2022)
TS101.8; An electromagnetic shielding metacomposite based on the absorbing mechanism was prepared by weaving ferromagnetic microwires into the three-dimensional (3D) fabric. The influence of the ferromagnetic microwire spacing on electromagnetic shielding performance and the electromagnetic shielding mechanism of 3D metacomposites were studied. The total electromagnetic shielding performance increases with the increase of electromagnetic wave frequency. 3D metacomposites based on the absorbing mechanism can avoid the secondary pollution of electromagnetic waves, and have great potential in military, civil, aerospace and other fields.